A Daring Life : A Biography of Eudora Welty - Brown, Carolyn J. (Book collections on Project MUSE., 2012)
"Mississippi author Eudora Welty--winner of the Pulitzer Prize and the National Book Award and the first living writer to be published in the Library of America series--mentored many of today's greatest fiction writers. This fascinating woman observed and wrote brilliantly throughout the majority of the twentieth century (1909-2001). Her life reflects a century of rapid change and is closely entwined with many events that mark our recent history. This biography tells Welty's story, beginning with her parents and their important influence on her reading and writing life. The chapters that follow focus on her education and her most important teachers as well as her life during the Depression and how her new career, just getting started, was interrupted by World War II. Throughout she shows independence and courage in her writing, especially during the turbulent civil rights period of the 1950s and 1960s. After years of care-giving and the deaths of all her immediate family members, Welty persevered, wrote acclaimed short stories, and won the Pulitzer Prize in 1973 for The Optimist's Daughter. Her popularity soared in the 1980s after she delivered the three William E. Massey Lectures to standing-room-only crowds at Harvard. The lectures were later published as One Writer's Beginnings and became a New York Times bestseller. This biography will introduce readers of all ages to one of the most significant writers of the past century, a prolific author who comprehends and transcends her Mississippi roots to create short stories, novels, and nonfiction that will endure for all time"--